Variables impacting young black women’s Entrepreneurship Intentions in the Eastern Cape of South Africa - Ikenna Franklin Eze; Thobekani Lose; Sinazo Mbebe (Cita Konsultindo Research Center, 2024)
There have been notable advancements in entrepreneurship research in the past few years with womens entrepreneurship quickly overtaking all other areas of interest in this discipline. Study on women entrepreneurs has primarily concentrated on already-existing enterprises and the variables influencing their success Despite the advancements in this field, it is essential to remember that women in this field have several traits that may further affect their intentions to engage in entrepreneurial activities Consequently, this research aimed to identify the variables impacting the entrepreneurial inclinations of young black women. A focus group was employed to gather information from the participants utilising qualitative interpretative analysis. Ten female participants took part in the focus group. The findings showed that, depending on several factors, young black women's intentions to start their own businesses differed. the data acquired in this study showed that participants believed that self-belief, resource availability, and family responsibilities were factors that affected young black women's intention to start their businesses.